Teaching responsible chemistry: a challenge-based learning framework for the implementation of RRI courses in tertiary chemistry education - Mehlich Jan (Chemistry Teacher International)
Responsible Research & Innovation (RRI) is a concept of professional attitude and agency in the context of innovation with significant expected societal and environmental impact. Yet, the realisation of RRI’s goals faces several methodological and structural difficulties, among them the insufficient implementation of RRI education in STEM majors at higher education institutions. This paper proposes a course concept that aims at filling a gap in the translation of RRI principles into tertiary chemistry education practice. Employing a challenge-based learning (CBL) approach, it draws on a practical framework of RRI as orientation for professional conduct in the context of chemistry (academic research, chemical engineering, and corporate R&D). The highly practical course – with lectures reduced to a minimum – is thematically structured around a fictitious innovation project as it may happen in real-world contexts, potentially in cooperation with local chemical companies and industry. Students form teams, define roles and shared values, identify a challenge of their interest, and are guided through developing and validating a solution. The CBL fashion is expected to lead to a high engagement with the course content, a clear realisation of the practical significance and applicability of the acquired skills, and a change in attitude towards normative dimensions of chemical science and innovation activities. The designated course objectives are the formation of normative literacy, the shaping of professional integrity and good scientific practice, the strengthening of discourse performance skills, and the ability of interdisciplinary collaboration in multi-stakeholder settings.